2012
DOI: 10.1080/14783363.2012.669541
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of the relationships within the categories of the EFQM model

Abstract: The relationships within the categories of the EFQM self-assessment model are analysed in this article, based on 242 independent assessments carried out in the European region with the highest density of EFQM awards (the Basque Autonomous Community, in Spain). The main finding of the article is that the relationships within the categories of the EFQM are robust, despite the fact that there exist relationships among some of its enablers and results that fail to reach a suitable level of validity. These findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
86
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 31 publications
7
86
0
3
Order By: Relevance
“…Asif et al (2013) noted that lack of content and internal validity in the education version of the BCPE is reflected in some critical weaknesses in the criteria. Contrary to these findings, some recent studies show that the BCPE and EFQM provide a valid operational framework for TQM implementation (Bou-Llusar et al, 2009;Heras-Saizarbitoria, Marimon, & Casadesus, 2012). Responding to the weaknesses of the BEMs, Dahlgaard et al (2013) developed a '4P' model for building organisational excellence that provides an augmented focus on the four critical areas of business excellence, namely 'people', 'partnership/teams', 'processes', and 'product/services'.…”
Section: Business Excellence Modelsmentioning
confidence: 80%
See 1 more Smart Citation
“…Asif et al (2013) noted that lack of content and internal validity in the education version of the BCPE is reflected in some critical weaknesses in the criteria. Contrary to these findings, some recent studies show that the BCPE and EFQM provide a valid operational framework for TQM implementation (Bou-Llusar et al, 2009;Heras-Saizarbitoria, Marimon, & Casadesus, 2012). Responding to the weaknesses of the BEMs, Dahlgaard et al (2013) developed a '4P' model for building organisational excellence that provides an augmented focus on the four critical areas of business excellence, namely 'people', 'partnership/teams', 'processes', and 'product/services'.…”
Section: Business Excellence Modelsmentioning
confidence: 80%
“…Thousands of organisations around the world use the BCPE and EFQM models (Heras-Saizarbitoria et al, 2012;Mann, Adebanjo, Laosirihongthong, & Punnakitikashem, 2011; National Institute of Standards and Technology [NIST], 2011). Further, these models provide a basic framework for the development of other models and quality awards.…”
Section: Business Excellence Modelsmentioning
confidence: 99%
“…Similar results, in regard to processes' application degree, were presented in relative studies that were carried out in public organizations (Institute of Agricultural Researches Cyprus, 2008) and in second degree educational institutions (Koltsakis, 2008). Also the results of studies which were carried out in companies, showed that most of the criteria were lower but close to medium level (Heras-Saizarbitoria et al, 2012) and the overall performance of the organizations surveyed was low (Lobo, Matawie & Samaranayake 2012). Low level quality practices and performances were also identified in research concerning quality performance evaluations of 3-, 4-, and 5-star hotels in Iran (Arasli, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Today, more than 80 national and state/regional awards base their frameworks upon the Malcolm Baldrige National Quality Award (MBNQA) criteria or the European Foundation for Quality Management (EFQM)/ European Excellence Award criteria , and around 30,000 European organizations were using the European Excellence Model in (Heras-Saizarbitoria, 2012.…”
Section: Introductionmentioning
confidence: 99%